1994
DOI: 10.1093/hmg/3.3.465
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a novel gene encoding nuclear protein at a locus (D11S636) tightly linked to multiple endocrine neoplasia type 1 (MEN1)

Abstract: To identify a gene responsible for multiple endocrine neoplasia type 1 (MEN1), we attempted to isolate potentially transcribable fragments from cosmid clones derived from a region on chromosome 11q13 where genetic linkage studies and analyses of loss of heterozygosity in MEN1-associated tumors have localized the MEN1 gene. By an exon-amplification method, we recovered three exon-like sequences from one of these clones, cCI11-367, and using these sequences as probes we were able to isolate new clones from cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…Two other proteins also show significant similarity to GLD-1, Sam68, and GRP33 (see Fig. 4): A predicted protein from C. elegans, BO280.11 (Wilson et al 1994), and ZFM1 from humans (Toda et al 1994). We confirmed that a gene is transcribed from the BO280.11 region by isolating and sequencing cDNA clones (see Materials and methods).…”
Section: Conserved Domains In the Gld-1 Predicted Proteinmentioning
confidence: 55%
See 2 more Smart Citations
“…Two other proteins also show significant similarity to GLD-1, Sam68, and GRP33 (see Fig. 4): A predicted protein from C. elegans, BO280.11 (Wilson et al 1994), and ZFM1 from humans (Toda et al 1994). We confirmed that a gene is transcribed from the BO280.11 region by isolating and sequencing cDNA clones (see Materials and methods).…”
Section: Conserved Domains In the Gld-1 Predicted Proteinmentioning
confidence: 55%
“…This small region, which we refer to as the CGA region, is just carboxy-terminal to the GSG domain and apparently not found in Sam68 and GRP33. This region, as well as a partial GSG domain, is also found in ZFM 1, a gene that is tightly linked to multiple endocrine neoplasia type 1 (MEN1) in humans (Toda et al 1994). Like the GSG domain, the CGA region is important for GLD-I function, as several gld-1 mutations affect it (refer to Table 1; and Fig.…”
Section: Gld-1 Has a Tumor Suppressor Function In Vivomentioning
confidence: 97%
See 1 more Smart Citation
“…Alignment of the KH domains (16,25) reveals a subfamily of KH-domain-containing proteins including human and murine Sam68 (29,45), Artemia salina GRP33 (6), C. elegans GLD-1 (19), mouse Qk1 (9), human ZFM1 (38), and predicted protein BO280.11b from C. elegans (44). Most recently, two additional members have been identified, including the mammalian splicing factor SF1 (1) and the Drosophila "held-out wings" gene product (GenBank accession no.…”
mentioning
confidence: 99%
“…At present only two genes, ZFM1 (Toda et al 1994) and FAU1 (Kas et al 1993a), have been assigned to the minimal MEN1 interval, PYGM-D11S449 . Both genes have been excluded as candidates for MEN 1 based on mutation analysis (Kas et al 1993b;Courseaux et al 1996).…”
mentioning
confidence: 99%